2016
DOI: 10.4236/jbm.2016.410004
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Role of Garlic and Bioactive Components in Cardiovascular and Cerebrovascular Health: What We Do Know

Abstract: Cardiovascular disease is a complex and multifactorial disease strongly associated with hypercholesterolemia, hypertension, reduced fibrinolysis, increased blood-clotting time and increased platelet aggregation. Among other confounding factors, oxidative damage is a major factor in cardiovascular and cerebrovascular diseases. The use of garlic in folkloric medicine highlights the potential role in either preventing or delaying cardiovascular disease. Contemporary research reveals how garlic and bioactive compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Down-regulation of TLR4 can decrease production of TNF-α. SCGO also contains ajoene that has anti-thrombosis and anti-aggregation activities by preventing binding of platelets to fibrinogen receptors that in turn prevents formation of thrombi in atherosclerosis disease (17). Here we showed that treatment of mice fed a HFD with SCGO could decrease TNF-α levels in serum compared to the negative control group given HFD alone.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Down-regulation of TLR4 can decrease production of TNF-α. SCGO also contains ajoene that has anti-thrombosis and anti-aggregation activities by preventing binding of platelets to fibrinogen receptors that in turn prevents formation of thrombi in atherosclerosis disease (17). Here we showed that treatment of mice fed a HFD with SCGO could decrease TNF-α levels in serum compared to the negative control group given HFD alone.…”
Section: Discussionmentioning
confidence: 58%
“…Single clove garlic oil (SCGO) extract is used as an herbal medicine that is thought to prevent and treat various diseases caused by HFD. Organosulfur in garlic can increase SOD activity and decrease secretion of pro-inflammatory cytokines such as TNF-α (17). The aims of this study were to determine whether SCGO extracts can ameliorate hepatic steatosis and improve oxidative status by decreasing levels of TNF-α and restoring superoxide dismutase levels in HFD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alliaceous vegetables are processed to different products such as dietary supplements, oil macerates, essential oils, powders, and extracts. These are available in numerous fresh and dehydrated products and are utilized in a wide range of medicine and dishes [ 91 ]. The dehydrated products are produced by the dehydration of alliaceous plants in hot air tunnels.…”
Section: Plant-derived Sulfur Compounds—gsls and Oscsmentioning
confidence: 99%
“…The use of medicinal plants to treat various health problems have received considerable attention since ancient times [1] and currently have applied in numerous industries such as pharmaceutical, chemical, food and cosmetic [2]. As an herbal medication, single garlic plays a role in overcoming various types of health problems, including an antithrombotic, antihypertensive, antiatherosclerosis, antihyperhomocysteinemic [3,4] and anticancer [5] effect. These benefits are due to the presence of organosulfur bioactive compounds [6,7].…”
Section: Introductionmentioning
confidence: 99%